KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 1 SIAK KECIL - Murni Murni; Abdul Razak; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is entitled the ability to write exposition text for class X students of SMA Negeri 1 Siak Kecil. The purpose of this paper is to know the high ability to write exposition text in class X of SMA Negeri 1 Siak Kecil. The method used is descriptive analysis method with a quantitative approach. This research data is the result of the score of the ability to write exposition text with an assessment rubric. The sampling technique in this study is total sampling, which is all students of class X SMA Negeri 1 Siak Kecil, amounting to 85 students. The results of the study found the ability to write exposition text of class X students of SMA 1 Siak Kecil in the low category as many as 25 students, the medium category was 56 students, the high category was 3 students, and the category was very high as many as 1 student.Key Words: Ability, Writing, Exposition Text.